Global role of the membrane protease LonB in Archaea: Potential protease targets revealed by quantitative proteome analysis of a lonB mutant in Haloferax volcanii - Cerletti, Micaela (2015)
The membrane-associated LonB protease is essential for viability in Haloferax volcanii, however, the cellular processes affected by this protease in archaea are unknown. In this study, the impact of a lon conditional mutation (down-regulation) on H. volcanii physiology was examined by comparing proteomes of parental and mutant cells using shotgun proteomics. A total of 1778 proteins were identified (44% of H. volcanii predicted proteome) and 142 changed significantly in amount (≥. 2 fold). Of these, 66 were augmented in response to Lon deficiency suggesting they could be Lon substrates. The "Lon subproteome" included soluble and predicted membrane proteins expected to participate in diverse cellular processes. The dramatic stabilization of phytoene synthase (57 fold) in concert with overpigmentation of lon mutant cells suggests that Lon controls carotenogenesis in H. volcanii. Several hypothetical proteins, which may reveal novel functions and/or be involved in adaptation to extreme environments, were notably increased (300 fold). This study, which represents the first proteome examination of a Lon deficient archaeal cell, shows that Lon has a strong impact on H. volcanii physiology evidencing the cellular processes controlled by this protease in Archaea. Additionally, this work provides a platform for the discovery of novel targets of Lon proteases. Biological Significance: The proteome of a Lon-deficient archaeal cell was examined for the first time showing that Lon has a strong impact on H. volcanii physiology and evidencing the proteins and cellular processes controlled by this protease in Archaea. This work will facilitate future investigations aiming to address Lon function in archaea and provides a platform for the discovery of endogenous targets of the archaeal-type Lon as well as novel targets/processes regulated by Lon proteases. This knowledge will advance the understanding on archaeal physiology and the biological function of membrane proteases in microorganisms.